Electric Power Converter with a Wide Input Voltage Range - K.O. Khokhlov; G.K. Khokhlov; A.V. Ishchenko; A.N. Cherepanov; A.S. Naronov (International Journal of Power Electronics and Drive Systems (IJPEDS), 2016)
The electric power converter for downhole telemetry systems of oil-well pumps include a downhole block connected to the pump that contains electronic circuits required for the operation of the motor pump sensors and transmission of data about their condition to the surface are described. A few methods of electric power conversion for this purpose are considered. The circuit contained two steps of voltage converting are proposed. The electrical scheme of this method is considered in the article. Proposed decisions are simulated and verified experimentally. The input high supply voltage range (200-4200 V) without loss of efficiency (even temporary) was obtained. The results of simulation and experimental studies have shown very close results.